Faces of Women’s Activists in the Parliament: Achievements and Political Recommendations - Aditya Perdana (Yayasan Jurnal Perempuan, 2014)
This article describes how seven female activists from civil organizations participate in 2004 and 2009 elections. On the frame of the implementation of women’s representation in parliament that has been started since 2004 election, this article unearths women’s representation movement based on the actors’ experiences to participate in election. Using case study method and analysis with process tracing, this article argues that women activists, who participated in two elections, have contributed to implement women’s representation into their political parties and parliament.